Transformation In Virtual Dance: The Existence Of Dance In The Dance Art Study Program - sama, iwayan (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
The article "Transformation in Virtual Dance: The Existence of Dance in the Dance Art Study Program "explained the change that occurs when a dance work performed on a performance stage is artistically transformed into a virtual dance work. This study employed a qualitative ethnographic methodology along with methodologies from observation, interviews, and literature study to explore the idea of metamorphosis in dance works. Following the completion of this research, it was evident that there had been a change in the character, situation, and presentation of virtual dance works in terms of form and presentation. The character feels light and instant while the situation clarifies that the virtual dance work can be viewed anytime, anywhere, and under any circumstances. The dance work's form is realized through editing a video recording document